A nonlinear macromodel for current-feedback operational amplifiers. Issue 10 (October 2015) - Ortega-Torres, E.; Ruíz-Hernández, S.; Sánchez-López, C.
Abstract This paper proposes a macromodel to emulate the nonlinear behavior of current-feedback operational amplifiers (CFOAs) at low-frequency. The main difference between this macromodel and those reported previously in the literature is that herein, real physical active device performance parameters along with parasitic elements associated to the input–output terminals of the amplifier are considered. To validate the deduced behavioral model, a saturated nonlinear function series (SNFS) based on CFOAs is built and numerical simulations are generated. In this point, the modeling problem is cast in terms of an augmented set of equations but that, unlike a piece-wise linear (PWL) approach, the dynamic behavior of each CFOA is considered. Afterwards, the SNFS is experimentally tested by using commercially available active devices, confirming good agreement among theoretical simulations and experimental tests at two operating frequencies and showing a better accuracy compared with a PWL approach and a linear model for CFOAs. Because the derived nonlinear macromodel for CFOAs is used for generating the behavioral model of the SNFS, one concludes that the latter is also both accurate and efficient with respect to traditional techniques, such as PWL approaches.